Main individual factors influencing the learning approaches: The first-year students’ perspective - Omar Jiyed; Ouafae Idrissi Aydi; Anouar Alami; Nadia Benjelloun; Moncef Zaki; Mohammed Lachkar (Institute of Advanced Engineering and Science, 2022)
Currently, the quality of student learning i.e. in-depth learning is essential in any planned reform. The massification phenomenon is one of the challenges facing this quality. This study explored the student characteristics influencing the learning process in an open access faculty, namely, the Dhar El Mahraz Faculty of Science in Fez, Morocco. Semi-structured interviews were conducted on 15 freshmen who enrolled in Earth and Universe Sciences and Life Sciences (EUS/LIS) program and presented a dominance of a surface learning approach. The main factors encouraging surface learning emerged were the learning habits and strategies, language competencies, motivational aspects and gender. The findings serve as an input for the design and implementation of actions to enhance deep learning.